Development and evaluation of a socially connected mobile application to increase fish consumption - White, James Angus (Curtin University, 2015)
Fish consumption is protective against many chronic diseases. A complex intervention approach was used to guide formative research, identifying barriers to consumption. This in turn guided the development of a socially connected mobile application that was evaluated in an exploratory trial. While overall fish consumption did not differ significantly between intervention and control groups, some patterns of application use were associated with increased consumption. Implications are discussed for the development and evaluation of mHealth interventions.